The palmitoyl acyltransferase HIP14 shares a high proportion of interactors with huntingtin: implications for a role in the pathogenesis of Huntington's disease. (4th April 2014) - Butland, Stefanie L.; Sanders, Shaun S.; Schmidt, Mandi E.; Riechers, Sean-Patrick; Lin, David T.S.; Martin, Dale D.O.; Vaid, Kuljeet; Graham, Rona K.; Singaraja, Roshni R.; Wanker, Erich E.; Conibear, Elizabeth; Hayden, Michael R.
Abstract : HIP14 is the most highly conserved of 23 human palmitoyl acyltransferases (PATs) that catalyze the post-translational addition of palmitate to proteins, including huntingtin (HTT). HIP14 is dysfunctional in the presence of mutant HTT (mHTT), the causative gene for Huntington disease (HD), and we hypothesize that reduced palmitoylation of HTT and other HIP14 substrates contributes to the pathogenesis of the disease. Here we describe the yeast two-hybrid (Y2H) interactors of HIP14 in the first comprehensive study of interactors of a mammalian PAT. Unexpectedly, we discovered a highly significant overlap between HIP14 interactors and 370 published interactors of HTT, 4-fold greater than for control proteins ( P = 8 × 10 −5 ). Nearly half of the 36 shared interactors are already implicated in HD, supporting a direct link between HIP14 and the disease. The HIP14 Y2H interaction set is significantly enriched for palmitoylated proteins that are candidate substrates. We confirmed that three of them, GPM6A, and the Sprouty domain-containing proteins SPRED1 and SPRED3, are indeed palmitoylated by HIP14; the first enzyme known to palmitoylate these proteins. These novel substrates functions might be affected by reduced palmitoylation in HD. We also show that the vesicular cargo adapter optineurin, an established HTT-binding protein, co-immunoprecipitates with HIP14 but is not palmitoylated. mHTT leads to mislocalization of optineurin and aberrant cargo trafficking. Therefore, it is possible that optineurin regulates trafficking of HIP14 to its substrates. Taken together, our data raise the possibility that defective palmitoylation by HIP14 might be an important mechanism that contributes to the pathogenesis of HD.